2017
DOI: 10.18178/ijiet.2017.7.9.952
|View full text |Cite
|
Sign up to set email alerts
|

Review on Blended Learning: Identifying the Key Themes and Categories

Abstract: Abstract-Blended learning is getting popular nowadays. Even though many studies have been conducted on online learning, studies specifically on blended learning are still scarce. This paper reports on a systematic literature review about blended learning of 103 journal research articles. The purpose of the review is to explore the status of blended learning research, and identify their themes and categories according to their contents. Twelve themes are identified of the articles examined in this paper. Findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 73 publications
0
27
0
4
Order By: Relevance
“…Like other reviews of blended learning research (Drysdale et al, 2013;Halverson et al, 2014;Zhang & Zhu, 2017), this review has shown the prevalence of research that focuses on learner outcomes. This chimes with Zhang and Zhu's recent observation that 'blended learning is still undergoing the beginning period so that most articles aimed at identifying the effectiveness of blended learning and designing blended learning' (2017, p.676).…”
Section: Approach Percentmentioning
confidence: 99%
See 1 more Smart Citation
“…Like other reviews of blended learning research (Drysdale et al, 2013;Halverson et al, 2014;Zhang & Zhu, 2017), this review has shown the prevalence of research that focuses on learner outcomes. This chimes with Zhang and Zhu's recent observation that 'blended learning is still undergoing the beginning period so that most articles aimed at identifying the effectiveness of blended learning and designing blended learning' (2017, p.676).…”
Section: Approach Percentmentioning
confidence: 99%
“…Building on earlier reviews of blended learning research (e.g. Bliuc, Goodyear, & Ellis, 2007;Drysdale et al, 2013;Halverson et al, 2012;Halverson, Graham, Spring, Drysdale, & Henrie, 2014;Zhang & Zhu, 2017), this article focuses on the use of the term blended learning within higher education research, where it is being used, how it is defined, how the field is being researched, and what this means for future development .…”
Section: Introductionmentioning
confidence: 99%
“…El blended learning es considerado una modalidad híbrida, pues combina y balancea los recursos más efectivos de la modalidad presencial y la virtual (Zhang y Zhu, 2017). Así, el aprendizaje toma lugar tanto en espacios físicos como virtuales, más aún, el aula virtual funciona como una extensión del aula física (Zhang y Zhu, 2017).…”
Section: Marco Teóricounclassified
“…El blended learning es considerado una modalidad híbrida, pues combina y balancea los recursos más efectivos de la modalidad presencial y la virtual (Zhang y Zhu, 2017). Así, el aprendizaje toma lugar tanto en espacios físicos como virtuales, más aún, el aula virtual funciona como una extensión del aula física (Zhang y Zhu, 2017). Esta modalidad tiene la finalidad de servir mejor las necesidades de los estudiantes y, sobre todo, brindarles una mayor diversidad de oportunidades de aprendizaje y así potenciar sus procesos educativos (Khan, 2015).…”
Section: Marco Teóricounclassified
“…In a recent study conducted by Zhang and Zhu (2017), they identified 103 published articles on blended learning. The most prevalent topics in this group of articles were design of blended learning (29) and evaluation (38) with research identifying models for blended learning design and assessing the effectiveness of blended learning.…”
Section: What Does the Research Tell Us About Blended Learning?mentioning
confidence: 99%